1985
DOI: 10.1097/00004032-198505000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Ingested U and Ra

Abstract: The literature on metabolism of U and Ra for man relevant to deriving drinking water standards has been reviewed and summarized. Radium is well understood, but significant gaps remain in our knowledge about U metabolism. Limits should be based on an equilibrium model where a constant relationship between intake and organ burden is established, using the best and most likely metabolic parameters. For the skeleton we conclude that the best estimate of skeletal burden expressed in days equivalent intake are 25 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
7

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(133 citation statements)
references
References 0 publications
2
122
0
7
Order By: Relevance
“…Like many trace metals the bioavailability of uranium in food may be influenced by the food's phytate (or fibre) content [19][20] and the presence of the low molecular weight ligands, such as citrate may promote uptake. Wrenn et al [21] reviewed uranium uptake factor across the range of average diets and suggested an uptake factor of 2% to 3%.…”
Section: Resultsmentioning
confidence: 99%
“…Like many trace metals the bioavailability of uranium in food may be influenced by the food's phytate (or fibre) content [19][20] and the presence of the low molecular weight ligands, such as citrate may promote uptake. Wrenn et al [21] reviewed uranium uptake factor across the range of average diets and suggested an uptake factor of 2% to 3%.…”
Section: Resultsmentioning
confidence: 99%
“…Uranium exposure has been found to be positively associated with cytotoxicity biomarkers: increases in urinary albumin [8], glucose and calcium [2], β2-microglobulin and alkaline phosphatase [6]. Absorbed uranium not excreted via urine, accumulates primarily in the skeleton and kidney [4,43]. Exposure can increase cancer risk and lead to liver damage [44].…”
Section: Uraniummentioning
confidence: 99%
“…Entretanto, para o urânio, a toxicidade química é maior que a radiológica, sendo os efeitos de toxicidade sistêmica o critério limitante no qual deve se basear o controle da exposição a este contaminante (Wrenn et al, 1985;Fisenne, Perry & Harley, 1988).…”
Section: Assessorando O Riscounclassified